The Importance of Cared for Diversity through Multicultural Education at School Medan - Aricindy, Argitha; Wasino, Wasino; Atmaja, Hamdan Tri (JESS (Journal of Educational Social Studies), 2023)
Multiculturalism is a concept that is addressed to a society in the context of nationality to recognize diversity, pluralism, and diversity of races, cultures, ethnicities, and religions. The purpose of this study is to describe the model of multicultural education at the Sultan Iskandar Muda educational foundation school and to examine further the concepts and practices of holistic multicultural education. The type of research conducted is qualitative research using an ethnographic approach. Locations conducted during the study were in the area around Medan at the Sultan Iskandar Muda College Foundation, Jalan Sunggal, the informants were appointed by the Principal, Teachers, Students. The results of this study are that the application of multicultural education at YPSIM provides a belief and explanation that examines and assesses the importance of cultural and ethnic diversity in lifestyle, social experience, personal identity, educational opportunities of individuals, groups and countries. The concept of holistic multicultural education can be seen through the school's vision and policies, leadership and management, capacity and culture and school culture. So that later multicultural education can be integrated with existing subjects in schools to realize the values of tolerance, pluralism, nationalism and anti-discrimination.